Economic Analyses Of Law - DE932 - 202102 - Ghersi Murillo, Lucas Daniel (2021)
What explains the details of our existing property, contracts, torts, and criminal laws, and how can we best think about institutional reforms? What is the proper role for democratic legislatures, courts, markets, federalism, and civil society? Which institutional arrangements allow a society to organize most productively, and why do many countries lack those institutions? This class uses the basic concepts and tools of economics to address such questions.